An unusual cause of pain in the finger - Arumugam, Manohar (Calicut Medical College, 2006)
Ganglions are the most common soft tissue tumour of the hand. Ganglion of the proximal interphalangeal joint however, is rare. Lack of knowledge of this condition caused delayed treatment of this patient. We report here a case of a ganglion of the proximal interphalangeal joint in a 43 year old Malay lady who was initially misdiagnosed.